MODELING AND TESTING OF AN ICE BANK FOR MILK COOLING AFTER MILKING - Rodrigo A. Jordan; Luís A. B. Cortez; Vivaldo Silveira Jr.; Mário E. R. M. Cavalcanti- Mata; Fellipe D. de Oliveira (Engenharia Agrícola, 2018)
ABSTRACT Based on mass and energy balance equations and data collected in specialized bibliographies, it was proposed a methodology for modeling of an ice bank for thermal storage of energy at low temperature to be used in milk cooling. The data obtained by the equations arrangement were used in the design and installation of a real system, which was tested to collect data and to compare it with the estimated. The data obtained in terms of prediction of ice formation, temperature of the ice bank, water and capacity of the selected refrigeration system prove the adequacy of the equations arrangement, showing that it can be used as a tool for sizing solid ice bank in smooth pipe coils, with good approximation.